1992
DOI: 10.1159/000282394
|View full text |Cite
|
Sign up to set email alerts
|

Venous Surgery in Erectile Dysfunction

Abstract: We report here on our surgical experience with venous leakage of the cavernous bodies. Out of 159 patients operated on, 134 were availabe for long-term follow-up. Depending on the cavernosographic findings, one of three different surgical procedures was carried out: ligation of the deep dorsal vein of the penis, spongiosolysis, or ligation of the crura. 18% of the patients undergoing ligation of the deep dorsal vein, postoperatively attained spontaneous erections, while 35% needed adjuvant corpus cavernosum au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In particular, Doppler interrogation of CSC can be useful in patients with high flow priapism, since these vessels can represent collaterals feeding the cavernosal fistula. Moreover, it has been demonstrated that veno-occlusive dysfunction is usually due to a pathology of the cavernous tissue [13,14,15,16,17,18] which cannot relax, rather than to pathological blood leakage through the outflow vascular pathways; however, blood leakage could exist, for instance, in pathological conditions such as severe Peyronie disease, or in posttraumatic albugineal scars, where the tunica albuginea cannot distend and trigger the veno-occlusive mechanism. Doppler investigation of CSC could be useful in these patients because these vessels are possible leakage pathways.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Doppler interrogation of CSC can be useful in patients with high flow priapism, since these vessels can represent collaterals feeding the cavernosal fistula. Moreover, it has been demonstrated that veno-occlusive dysfunction is usually due to a pathology of the cavernous tissue [13,14,15,16,17,18] which cannot relax, rather than to pathological blood leakage through the outflow vascular pathways; however, blood leakage could exist, for instance, in pathological conditions such as severe Peyronie disease, or in posttraumatic albugineal scars, where the tunica albuginea cannot distend and trigger the veno-occlusive mechanism. Doppler investigation of CSC could be useful in these patients because these vessels are possible leakage pathways.…”
Section: Resultsmentioning
confidence: 99%
“…21 Vascular surgery consisted in both arterial reconstructive surgery 22 or venous surgery such as Selective Vein Ligation (SVL) of veins identified as incontinent. 23 Penile prostheses used in this study were inflatable self-contained prostheses. 24 Finally, commercial vacuum constriction devices were used.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan (1974). Vascular surgery consisted of both arterial reconstructive surgery (Levine & Goldstein, 1990) or venous surgery such as Selective Vein Ligation (SVL) of veins identi®ed as incontinent (Gilbert et al, 1992). Penile prostheses used in this study were in¯atable self-contained prostheses (Petrou & Barret, 1990).…”
Section: Hormone Pro®le At Entrymentioning
confidence: 99%